Joseph Neng Shun Kwong: a famous and obscure scientist - Simón Reif-Acherman (Química Nova, 2008)
Many students and professionals in chemistry and chemical engineering related the name Kwong with one of the most remarkable equations of state with two parameters. In the same way, very few people know who Kowng was. This article shows some of the unknown personal and professional facts of Joseph Neng Shun Kwong, a person who devoted almost four decades of his life to the industrial research in the adhesives industry.